Adapting by altering: spatial modifications of terraced houses in the Klang Valley area / Erdayu Os’hara Omar, Esmawee Endut and Masran Saruwono - Omar, Erdayu Os’hara; Endut, Esmawee; Saruwono, Masran (Universiti Teknologi MARA Cawangan Selangor, 2017)
This paper presents the initial findings of a study on the spatial modifications of fifty houses by homeowners in the Klang Valley area. Using a standardised format, various attributes consisting altered spaces and features were compiled and examined. It appears that certain features of the houses including kitchen, bedrooms and bathrooms were desperately altered. People have used their creativity in altering the spaces beyond the original intentions of the architect. To some extent, the findings indicate that the current model for providing houses has shortcomings in addressing the need to satisfy the aspirations of individual family to living.